Microbiological safety aspects of mangoes (Mangifera indica) and papayas (Carica papaya): a mini-review - Ana Lucia Penteado (Fundação Oswaldo Cruz (FIOCRUZ), 2017)
This review describes several aspects related to microbiological safety in mangoes and papayas, such as incidence, outbreaks, internalisation and growth/survival of bacterial pathogens. Mangoes and papayas are often served sliced in food establishments in fresh pieces at salad bars, deli counters and as pulp juice. In general, these products do not undergo any process to eliminate pathogenic microorganisms before consumption, and a long shelf life could theoretically provide time for these microorganisms to multiply without affecting the organoleptic qualities of the fruit, thereby increasing the risks of food-borne illness. The data presented in this review show that low temperatures can impede microbial growth, but not completely inhibit such growth in mangoes and papayas. Highest growth rates were observed in the range between 22 and 37oC. In the last 20 years, several outbreaks of salmonellosis caused by these fruits or by food made with these fruits have been reported. The control of the temperature in the fruit washing water is important to prevent the internalisation of Salmonella spp. The implementation of strategies such as Good Agricultural Practices, Good Manufacturing Practices and Hazard Analysis Critical is important, as these methods can eliminate or significantly reduce microbial contamination.